Persepsi Akuntan, Mahasiswa Akuntansi, dan Karyawan Bagian Akuntansi terhadap Etika Profesi Akuntan (Survey di Surakarta) - Muhamat Yusup; Sri Suranta; Muhammad Syafiqurrahman (Jurnal Akuntansi dan Bisnis, 2007)
This research aims to know the different perception among accountants, accounting students and accounting department staffs about accountant profession ethic. This research referred to Ethical Principle that is used by Indonesian Accountant Association. The populations of this research are accountants (lecturer, CPA), accounting students in private and public university located in Surakarta, and companies accounting department staff located in Surakarta. This research used purposive sampling method to collect samples. The test to examine the hypothesis was Kruskal Wallis Test. The result of perception to accountant profession ethic hypothesis through Kruskal Wallis Test showed the existence of different perception which significant among accountants, accounting students and accounting department staffs with p value 0.05. This research’s result consistent with Wulandari dan Sularso (2002). Based on the analysis result, the mean value from each group samples of accountant professional ethic indicated that the mean value for perception of accountants was highest than accounting students and accounting department staffs. Accountants have better perception of accountant profession ethic than others.